2009
DOI: 10.1097/tp.0b013e31818bd790
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Antibodies Against HLA, MICA, and GSTT1 in Patients with Allograft Rejection and C4d Deposition in Renal Biopsies

Abstract: Besides anti-HLA antibodies, donor-specific antibodies against MICA and GSTT1 antigens could be responsible for the occurrence of antibody-mediated kidney graft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 23 publications
3
39
1
1
Order By: Relevance
“…5 These finding were confirmed by Alvarez-Marquez et al 10 who showed that in eight renal transplants performed in the context of a GSTT1-positive donor/GSTT1-negative recipient, which resulted in graft dysfunction and CD4 þ deposition in the kidney, 75% of the recipients developed anti-GSTT1 antibodies. In three of these, no other donorspecific HLA I/II or MHC class I chain-related gene A (MICA) antibodies were detected.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…5 These finding were confirmed by Alvarez-Marquez et al 10 who showed that in eight renal transplants performed in the context of a GSTT1-positive donor/GSTT1-negative recipient, which resulted in graft dysfunction and CD4 þ deposition in the kidney, 75% of the recipients developed anti-GSTT1 antibodies. In three of these, no other donorspecific HLA I/II or MHC class I chain-related gene A (MICA) antibodies were detected.…”
Section: Discussionsupporting
confidence: 75%
“…9 In GSTT1-null kidney transplant patients with a GSTT1-positive donor, an association between chronic humoral kidney rejection and post-transplant production of anti-GSTT1 antibodies has been demonstrated. 10 Renal biopsies of four patients with a GSTT1 donor/recipient mismatch, who developed anti-GSTT1 antibodies, showed pathological lesions compatible with chronic Ab-mediated rejection. In three of these patients, C4d þ staining in peritubular capillaries was also found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of the unavailability of pretransplant sera, we could not determine whether these antibodies were preexisting or de novo. Further investigations are warranted to address these remaining questions and to verify reported findings, namely, whether MICA antibodies are donor specific, 14 preexisting, or de novo, and to elucidate the relation between HLA antibodies and MICA antibodies. 4,15 …”
Section: Discussionmentioning
confidence: 99%
“…Serologic studies have demonstrated tight associations of antibody detection applying flow cytometry and complement-dependent cytotoxicity (CDC) testing with biopsy-based features of AMR [7][8][9][10]37]. However, such associations may be far from perfect.…”
Section: Antibody Detection In Patients With Graft Dysfunctionmentioning
confidence: 99%